2020
DOI: 10.1101/2020.09.25.311803
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

METTL3 inhibitors for epitranscriptomic modulation of cellular processes

Abstract: The methylase METTL3 is the writer enzyme of the N6-methyladenosine (m6A) modification of RNA. Using a structure-based drug discovery approach, we identified a METTL3 inhibitor (UZH1a) with potency in a biochemical assay of 280 nM, while its enantiomer UZH1b is 100 times less active. The crystal structure of the complex of METTL3 with UZH1a illustrates the interactions that make it selective against protein methyltransferases. We observed a dose-dependent reduction in m6A methylation level of mRNA in several c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…UPLC-MS/MS was performed as previously described. 28 Briefly, MOLM-13 cells were seeded into 6 well plates at a density of 1x10 6 cells/mL in 2 mL of complete RPMI medium. Cells were treated with the indicated concentrations of compounds or DMSO control (final concentration 0.5 % (v/v)) for 24 h. Following the incubation, cells were collected by centrifugation and washed once with PBS, and total RNA was extracted using 0.5 mL of GENEzol™ reagent according to the manufacturer's instructions.…”
Section: Quantification Of M6a/a Ratio In Polyadenylated Rna By Uplc-...mentioning
confidence: 99%
See 1 more Smart Citation
“…UPLC-MS/MS was performed as previously described. 28 Briefly, MOLM-13 cells were seeded into 6 well plates at a density of 1x10 6 cells/mL in 2 mL of complete RPMI medium. Cells were treated with the indicated concentrations of compounds or DMSO control (final concentration 0.5 % (v/v)) for 24 h. Following the incubation, cells were collected by centrifugation and washed once with PBS, and total RNA was extracted using 0.5 mL of GENEzol™ reagent according to the manufacturer's instructions.…”
Section: Quantification Of M6a/a Ratio In Polyadenylated Rna By Uplc-...mentioning
confidence: 99%
“…To date, only three series of SAM-competitive, potent, and selective inhibitors of METTL3 have been reported, two of them originating from medicinal chemistry campaigns carried out in our group at the University of Zurich (UZH). [27][28][29][30] The low nanomolar inhibitors UZH2 and the compound published by Storm Therapeutics (STM2457) have shown antiproliferative effects in acute myeloid leukemia (AML) cell lines, strengthening the therapeutic potential of targeting the METTL3-14 complex. 27,29 A small molecule inhibitor of METTL3 called STC-15 (SAM-competitive, developed by Storm Therapeutics) is currently in phase 1 clinical trials (https://clinicaltrials.gov/study/NCT05584111).…”
Section: Introductionmentioning
confidence: 99%
“…Since METTL3 has been linked to the initiation and maintenance of AML, two other studies have examined the cellular activity of a new METTL3 inhibitor for use in treating AML. One study has identified a METTL3 inhibitor (UZH1a) that showed potency at a 280 nM concentration in a biochemical assay [ 127 ]. UZH1a fills the pocket of the adenosine moiety of SAM but not the pocket of the SAM methionine, which makes it more selective of METTL3 than other SAM-dependent MTases.…”
Section: Inhibitors Of M6a Methyltransferasesmentioning
confidence: 99%
“…UZH1a fills the pocket of the adenosine moiety of SAM but not the pocket of the SAM methionine, which makes it more selective of METTL3 than other SAM-dependent MTases. The effect of METTL3 inhibition by UZH1a directly translates into m6A level depletion and impaired growth of MOLM13 leukemia cells [ 127 ]. Another group reported a more exciting study showing the first-in-class catalytic inhibitor of METTL3 (STM2457) (shown in Fig.…”
Section: Inhibitors Of M6a Methyltransferasesmentioning
confidence: 99%
“…9,10 Our research group has made recent contributions to this field through the development of small-molecule inhibitors targeting METTL3/14, demonstrating the modulation of interconnected cellular events. 11,12 Recognition of the m6A modification is mediated by "readers" that subsequently impact downstream processes. 13 The YTH family, comprising five proteins (YTHDC1, YTHDC2, and YTHDF1-3), is the best characterized family of m6A readers.…”
Section: Introductionmentioning
confidence: 99%